2016
DOI: 10.5301/jbm.5000205
|View full text |Cite
|
Sign up to set email alerts
|

Serum Markers Measured in FNA Fluids of Medullary Thyroid Carcinoma Occurring as a Cyst

Abstract: In the presence of a cystic thyroid lesion the diagnosis of MTC should be taken into account, and measuring calcitonin in FNA fluid is relevant. The determination in FNA of other markers is technically feasible but its role should be evaluated in larger series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…To date, only one paper has been published on the use of ProCT in the washout fluids from FNAC ( 21). In that case report, we showed that the determination of ProCT in FNAC from an MTC is technically feasible, even if this finding should be evaluated in larger series.…”
Section: Discussionmentioning
confidence: 85%
“…To date, only one paper has been published on the use of ProCT in the washout fluids from FNAC ( 21). In that case report, we showed that the determination of ProCT in FNAC from an MTC is technically feasible, even if this finding should be evaluated in larger series.…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, the number of cases with negative serum CT is negligible, and most of these were undifferentiated tumors or microcarcinomas [6,90,91]. On the other side, this measurement seems reliable also in MTC with ultrasound presentation as pure cyst [92].…”
Section: Samplingmentioning
confidence: 92%
“…10 Cystic MTC is a rare clinical presentation with only a few cases reported. 11 FNA diagnosis of MTC can be difficult due to the variety of cytomorphological appearances, as it exhibits cellular pleomorphism, with small cells, elongated cells, and plasmacytoid cells with eccentric nuclei. The nuclei are small and round to elongated, sometimes binucleated, with finely granular chromatin patterns typical of neuroendocrine tumours.…”
Section: Ys Ti C Thyroid Le S I On Smentioning
confidence: 99%